Public panic over Covid-19 Outbreak: Criticism toward panic theory in collective behavior study - Rochadi, AF Sigit; Nur Amalina Putri; Zaky Arsy Fauzi (Technium Social Sciences Journal, 2020)
This article evaluates the issue of public panic over the coronavirus outbreak in Indonesia from March to April 2020. The study was conducted with secondary data analysis sourced from competent online media, and was aimed to expand the panic scope as well as criticize the related theories in a collective behavior study. The results showed inconsistencies in the event of public panic in a crowd. This include while dealing with natural disasters, terror, sinking ships, fires, collapsed buildings or other physical threats, and also over invisible dangers, as observed with viruses. In addition, the individual disposition persists for a long time on occasions where the authorities, both political and academic, fail to immediately strategize a convincing countermeasure. Based on these findings, the study provides a critique of several theories, comprising crowd panic, emerging norms, and moral panic.